2012
DOI: 10.1177/1524839912458107
|View full text |Cite
|
Sign up to set email alerts
|

Using Social Marketing to Increase Awareness of the African American Infant Mortality Disparity

Abstract: Social marketing is an effective tool to increase disparity awareness, especially among groups disproportionately affected by the disparity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…From these 23 publications, over half of the studies (14/23) were conducted in the USA (26,28,30,33,35,37,(40)(41)(42)(43)(44)(45)(46)(47), four in New Zealand (25,29,32,38), three in the UK (31,34,39), and two in Australia (27,36). The studies span 14 years from 2005 to 2019 and the overall quality scores ranged from 23 to 83%, with 20/23 papers scoring 50% and above.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From these 23 publications, over half of the studies (14/23) were conducted in the USA (26,28,30,33,35,37,(40)(41)(42)(43)(44)(45)(46)(47), four in New Zealand (25,29,32,38), three in the UK (31,34,39), and two in Australia (27,36). The studies span 14 years from 2005 to 2019 and the overall quality scores ranged from 23 to 83%, with 20/23 papers scoring 50% and above.…”
Section: Resultsmentioning
confidence: 99%
“…All five studies in this section were conducted in the USA (40)(41)(42)(43)(44); two were evaluations (40,41), two were pre and posttest designs (42,43) and one tele-survey (44). The focus of these studies was on health education or raising awareness, and although Ahlers-Schmidt et al (40) provided a cot to participants, this was not the focus of their study.…”
Section: Health Education/raising Awareness Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Rienks et al in 2013 in San Francisco, social marketing techniques were used to develop and implement three campaigns to increase awareness regarding infant mortality disparities and proper infant sleep position and to take action to reduce disparities. This study showed social marketing is an effective tool to increase disparity awareness, especially among groups disproportionately affected by the disparity [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This has led to calls for assimilation of ideas and a joining of forces between social marketing and social movements (Daellenbach and Parkinson, 2017;Wymer, 2011). Researchers working in public health have identified how the use of social marketing tactics such as advertising and media advocacy can be used to raise awareness about health inequalities as a precursor to developing social movements to improve child health in the USA (see Rienks and Oliva, 2013). They note that awareness raising is an important step in building social movements (Tajfel and Turner, 1986).…”
Section: Social Marketing and Social Movementsmentioning
confidence: 99%